(untitled) (Kairaranga, 2008)
Much has happened since nine teams across New Zealand engaged in a Ministry of Education-funded participatory action research project looking at effective practice for supporting children and young people with autism spectrum disorder (ASD) in education. Building on earlier discussions, the project ran from 2002 to 2004, and until now the story has never been told in full. This article is intended to provide a background to the project, describe the project from a national perspective, profile the teams and their work and share some of the achievements and challenges.